Features of the development of running tourism in Russia based on the example of the ‘Pharmeco – Running along the Golden Ring’ project - Shvetsov, A.V. (Theory and Practice of Physical Culture, 2026)
Abstract Objective of the study is to identify the characteristics of the development of running tourism in Russia, using the example of the series of mass runs ‘Pharmeco – Running along the Golden Ring’. Methods and structure of the study. An analysis and summary of data from specialised and scientific-methodological literature has been conducted. Results and conclusions. The first running tourism project in Russia was a series of races called ‘Pharmeco – Running along the Golden Ring’. The races take place in cities along the popular Golden Ring tourist route and in other cities in central Russia that have preserved significant historical and cultural monuments, as well as unique natural sites. This sports and tourism project was launched in 2015 and since then has attracted and united not only professional runners, but also running enthusiasts, supporters of a healthy lifestyle and running tourism from different parts of the country.